Lithium supplement agent, preparation method thereof and all-solid-state battery
By using Li2O-M@Li3PO4 as lithium supplement agent in lithium-ion batteries, using metal elements to insert lithium vacancy and Li3PO4 coating technology, the problem of low kinetic performance of existing lithium supplement materials is solved, the conductivity and kinetic performance is improved, and the energy density and cycle life of the battery are improved.
Patent Information
- Application Number
- CN202411894641.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
AI Technical Summary
Li2O, a lithium-enhancing material for existing lithium-ion batteries, has problems such as low kinetic performance, low specific capacity and poor conductivity, making it difficult to effectively improve the energy density and cycle life of the battery.
Li2O-M@Li3PO4 is used as the lithium supplement agent, where M is a metal element. By inserting the metal element into the lithium vacancies, part of the lattice distortion and lithium vacancies are formed, kinetic activity is improved, and chemical stability is improved through Li3PO4 coating.
The conductive, dynamic performance and lithium ion removal capability of lithium supplement agents are improved, the first round overpotential and Li-O bond energy are reduced, and the energy density and cycle life of the battery are enhanced.
Smart Images

Figure CN119650657A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of all-solid-state batteries, and in particular to a lithium supplement and a preparation method thereof, and an all-solid-state battery. Background Art
[0002] In order to solve the first irreversible capacity loss of lithium-ion batteries and improve the energy density of batteries, the use of positive and negative electrode pre-lithiation is one of the indispensable means. The role of lithium replenishment materials is to offset the active lithium produced by the solid electrolyte interface film and consumed by side reactions during the first cycle of charging of the all-solid-state battery. Compared with the negative electrode lithium replenishment technology, the positive electrode lithium replenishment method is simpler and safer. However, the current lithium replenishment material Li2O lithium replenisher has the problems of low kinetic performance, low specific capacity and poor conductivity. Summary of the invention
[0003] In view of the above problems, the object of the present invention is to provide a lithium supplement having excellent conductivity, high specific capacity and excellent kinetic performance, a preparation method thereof and an all-solid-state battery. The technical scheme is as follows:
[0004] On the one hand, a lithium supplement is provided, wherein the chemical formula of the lithium supplement is Li2O-M@Li3PO4, wherein M is a metal element.
[0005] In an exemplary embodiment, the M includes one of Group VB or Group VIII.
[0006] On the other hand, the present invention also provides a method for preparing a lithium supplement, the method comprising:
[0007] Providing a raw material, wherein the raw material includes Li2O and LiMPO4;
[0008] mixing the raw materials to obtain an intermediate product;
[0009] The intermediate product is placed in an inert gas atmosphere for heat treatment to obtain the lithium supplement agent.
[0010] In an exemplary embodiment, the mass ratio of the Li2O to the LiMPO4 is 1:(0.1-1.0).
[0011] In an exemplary embodiment, the mixing of the raw materials to obtain an intermediate product comprises:
[0012] The raw materials are mixed by ball milling to obtain an intermediate product;
[0013] The rotation speed of the ball mill is 100 to 300 rpm;
[0014] The ball milling time is 30 to 70 hours.
[0015] In an exemplary embodiment, the mass ratio of the raw material to the ball milling balls is 1:(10-40).
[0016] In an exemplary embodiment, the heating rate of the heat treatment is 1-5° C. / min.
[0017] In an exemplary embodiment, the heat treatment is performed at a temperature of 500-800°C.
[0018] In an exemplary embodiment, the heat treatment time is 5 to 15 hours.
[0019] On the other hand, an all-solid-state battery is provided, comprising any one of the above-mentioned lithium supplements.
[0020] The invention discloses a lithium supplement agent, the chemical formula of which is Li2O-M@Li3PO4, wherein M is a metal element. By inserting metal elements into lithium vacancies, the partial lattice distortion and lithium vacancies formed are beneficial to improving the kinetic activity, and the introduction of metal elements has a positive effect on the gradual breaking of Li-O bond energy, and promotes the release of lithium elements in Li2O, thereby realizing metal element doping modification, reducing the first-cycle overpotential, reducing Li-O bond energy, and improving the lithium ion release ability, thereby improving the conductivity of the lithium supplement agent; Li3PO4 coating can improve the chemical stability between the lithium supplement agent and the solid electrolyte, reduce side reactions, and improve the kinetic performance of the lithium supplement agent, thereby improving the solid electrode / solid electrolyte bulk and interface ion transmission capabilities based on the lithium supplement agent. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solution of the present invention, the following briefly introduces the drawings required for use in the embodiments or prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 This is a flow chart of a method for preparing a lithium supplement provided by an embodiment of the present invention;
[0023] Figure 2 This is an EDS image of Li2O-Fe@Li3PO4 provided in an embodiment of the present invention;
[0024] Figure 3 This is a relationship diagram between the number of cycles and specific capacity of solid-state batteries containing Li2O-Ni@Li3PO4, Li2O-V@Li3PO4, Li2O-Co@Li3PO4, Li2O-Fe@Li3PO4 and solid-state batteries without lithium supplement provided in the embodiments of the present invention. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] In order to solve the first irreversible capacity loss of lithium-ion batteries and improve the energy density of batteries, pre-lithiation of positive and negative electrodes is one of the indispensable means. Compared with the negative electrode lithium replenishment technology, the positive electrode lithium replenishment method is simpler and safer. Its operation method is mainly to mix the lithium replenishment material and the positive electrode in a certain proportion during homogenization and stir them evenly. The role of the lithium replenishment material is to offset the active lithium consumed by the generation of the interface SEI (solid electrolyte interface) film and side reactions during the first cycle of charging.
[0027] However, current lithium supplement materials have problems such as high decomposition voltage and poor conductivity. In particular, solid-phase synthesized lithium supplement materials have large particle sizes, long lithium ion transmission distances, and poor kinetic properties. Therefore, it is difficult to improve the conductivity and kinetic properties of materials by simply doping with metal oxides. In addition, although polymer coating can improve the air stability of materials, the inherent insulation of polymers greatly inhibits the improvement of the conductivity of lithium supplements, which is not conducive to the improvement of the kinetic properties of materials. Therefore, how to provide a lithium supplement material with high electrochemical activity and excellent kinetic properties has become the key.
[0028] An embodiment of the present application provides a lithium supplement, the chemical formula of the lithium supplement is Li2O-M@Li3PO4, wherein M is a metal element.
[0029] Specifically, by inserting metal elements into lithium vacancies, the partial lattice distortion and lithium vacancies formed are beneficial to improving the kinetic activity and promoting the release of lithium ions in Li2O. Moreover, the introduction of metal elements has a positive effect on the gradual breaking of Li-O bond energy. By forming Li3PO4 coating, the chemical stability between the lithium supplement and the solid electrolyte can be improved, the side reactions can be reduced, and the kinetic performance of the lithium supplement can be improved, thereby improving the bulk and interface ion transport capabilities of the solid electrode / solid electrolyte based on the lithium supplement.
[0030] In the embodiment of the present application, M includes one of group VB or group VIII.
[0031] Specifically, the elements in Group VB or Group VIII in the periodic table are transition metal elements, and transition metal compounds have higher specific capacity. For example, by selecting LiFePO4 as a raw material, iron is introduced into the Li2O lithium supplement to form Li2O-Fe@Li3PO4, wherein the price of the LiFePO4 raw material is low, the preparation cost of the lithium supplement is low, and it is conducive to large-scale production.
[0032] The present application also provides a method for preparing a lithium supplement. Figure 1 , Figure 1 The present invention is a flow chart of a method for preparing a lithium supplement, the method comprising the following steps:
[0033] Step S1: providing raw materials, the raw materials comprising Li2O and LiMPO4.
[0034] Among them, Li2O raw materials are a kind of positive electrode lithium supplement material with high potential in the battery preparation process because of their low cost and simple preparation process. Specifically, Li2O decomposes during the charging process, and the lithium ions released provide additional lithium ions to compensate for the active lithium consumed by the SEI formed by the negative electrode in the initial cycle, which plays a role in lithium supplementation, thereby improving the energy density and cycle life of the battery. However, due to the poor conductivity and low electrochemical activity of Li2O itself, it is difficult for Li2O to release its high theoretical capacity in practical applications. At present, although there are limitations in the application of Li2O as a lithium supplement material in batteries, its conductivity and electrochemical activity can be improved by doping with metal elements, thereby improving the energy density and cycle life of the battery.
[0035] Therefore, Li2O can be doped with metal elements by selecting metal salt compounds as raw materials. For example, lithium phosphate salt containing two metal elements is selected as the raw material for doping with metal elements. It is not only doped with metal elements, but also introduces lithium phosphate which has conductive properties to cover Li2O.
[0036] Step S2: Mix the raw materials to obtain an intermediate product.
[0037] Specifically, the method of mixing Li2O and LiMPO4 can be selected according to specific needs, and a grinder or a ball mill can be used.
[0038] Step S3: placing the intermediate product in an inert gas atmosphere for heat treatment to obtain a lithium supplement.
[0039] Specifically, during the preparation process of the lithium supplement, in order to prevent it from becoming ineffective in an air environment, it is necessary to synthesize it under an inert gas. Commonly used inert gases such as nitrogen or argon do not participate in chemical reactions and will not react with the lithium supplement or raw materials, thereby providing an ideal synthesis environment. The introduction of the inert gas can provide an oxygen-free and water-free environment to prevent the lithium supplement from being oxidized or hydrolyzed during the synthesis process. It can also reduce impurities that may be generated during the synthesis process, improve the purity of the lithium supplement, and avoid the influence of impurities on the electrochemical properties of the lithium supplement, thereby improving the performance of the lithium supplement.
[0040] In the embodiment of the present application, the mass ratio of Li2O to LiMPO4 is 1:(0.1-1.0).
[0041] Specifically, the amount of doped metal elements is regulated by controlling the mass ratio of the raw materials Li2O and LiMPO4, so as to achieve the purpose of improving the conductive properties of the lithium supplement.
[0042] In the embodiment of the present application, the raw materials are mixed to obtain an intermediate product comprising:
[0043] The raw materials are mixed by ball milling to obtain an intermediate product;
[0044] The ball milling speed is 100-300 rpm;
[0045] The ball milling time is 30 to 70 hours.
[0046] On the one hand, in the embodiments of the present application, the material of the ball milling ball can be one of zirconium oxide, stainless steel, and tungsten carbide. Specifically, the ball milling ball made of zirconium oxide has the advantages of high hardness, high density, wear resistance and impact resistance, good toughness, not easy to break, and no pollution to the sample. The ball milling ball made of zirconium oxide can mix a variety of samples, and the ball milling ball of this material also has the advantages of low wear and high grinding efficiency. The ball milling ball made of stainless steel ball has the advantage of acid resistance, but the stainless steel ball milling ball has the possibility of causing metal contamination to the mixed sample. When the ball mill is running at high speed, some metal impurities in the ball milling jar may be mixed with the mixed sample. In the embodiments of the present application, the lithium supplement with strict purity requirements can be mixed without using stainless steel ball milling balls during the preparation process to avoid the introduction of some metal impurities affecting the performance of the lithium supplement. The ball milling balls made of tungsten carbide have a black hexagonal crystal structure, a high melting point, excellent chemical stability, good electrical and thermal conductivity, strong impact resistance and wear resistance. Compared with zirconium oxide ball milling balls, tungsten carbide ball milling balls are more excellent in hardness and wear resistance, but in terms of chemical stability and avoiding contamination of samples, zirconium oxide ball milling balls are more excellent than tungsten carbide ball milling balls. In short, zirconia ball milling balls have the advantages of highly pure and pollution-free grinding; stainless steel ball milling balls have the advantages of acid resistance; and tungsten carbide ball milling balls have the advantages of excellent hardness and wear resistance. Therefore, when preparing the lithium supplement agent in the embodiment of the present application, the ball milling balls of suitable materials can be selected according to the actual requirements of the specific lithium supplement agent and taking into account the specific raw materials. Exemplarily, zirconia ball milling balls are selected for raw material mixing to avoid contamination by impurity metals, thereby ensuring the purity of the lithium supplement agent.
[0047] On the other hand, the size of the ball mill is selected from one or more of φ1mm, φ3mm, and φ5mm; when selecting the size of the ball mill, it is necessary to consider multiple factors such as the particle size, hardness, fineness of the raw materials to be mixed, and the rotation speed of the ball mill. Specifically, in the embodiment of the present application, when the particle size of the raw material is large, it is necessary to select a grinding ball with a larger diameter to provide sufficient crushing force. In the embodiment of the present application, the particle size of the raw material is small, that is, it is necessary to select a grinding ball with a smaller diameter to meet the needs of ball milling. This is because the large ball mill has a large weight and a large impact force on the raw material, which can be used to crush coarse and hard raw material particles; the small ball mill has a small volume and a large number of impacts, which can be used to further refine the raw material with smaller particles. Specifically, in the embodiment of the present application, a ball mill of a suitable size can be selected according to the properties of the raw material itself. On the other hand, the rotation speed of the ball mill has an important influence on the degree of refinement of the raw material and the degree of mixing uniformity during the mixing process. In the embodiment of the present application, the effect of raw material mixing can be improved by adjusting the rotation speed of the ball mill; at the same time, by controlling the time of the ball mill, the particle size can be reduced and the uniformity of raw material mixing can be improved.
[0048] The embodiment of the present application realizes the metal element doping modification of the Li2O lithium supplement by ball milling. By means of high-energy ball milling to break up the material lattice and refine the matrix particle size, the effect of uniform element doping and particle size refinement can be efficiently obtained. By ball milling the mixed raw materials, not only the particle size of Li2O can be reduced, but also the metal elements can be inserted into the lithium vacancies. The partial lattice distortion and lithium vacancies formed are beneficial to improving the kinetic activity and promoting the release of lithium ions in Li2O. Moreover, the introduction of metal elements has a positive effect on the gradual breaking of Li-O bond energy.
[0049] In the embodiment of the present application, the mass ratio of the raw material to the ball milling balls is 1:(10-40).
[0050] Specifically, the mass ratio of raw materials to ball milling balls is a key factor affecting the raw material mixing effect. Adjustment of this mass ratio directly affects the shear stress and impact frequency of the raw materials, thereby affecting the raw material mixing effect. Too few ball milling balls will lead to insufficient raw material mixing. Too large a ball milling ball will also lead to uneven raw material mixing, increased energy consumption, and the problem of introducing more impurities. During ball milling, an appropriate mass ratio of raw materials to ball milling balls is selected to achieve the purpose of improving the mixing effect. The embodiment of the present application selects ball milling balls of appropriate quality according to the specific feed amount, thereby improving the effect of the grinding balls on raw material mixing and improving the efficiency of the ball mill.
[0051] In the embodiments of the present application, the heating rate of the heat treatment is 1 to 5°C / min.
[0052] Specifically, the embodiments of the present application take into account that a too high heating rate of the heat treatment may mainly cause the LiMPO4 material structure to be destroyed, the performance to be reduced, and a large stress and strain to be generated. A low heating rate will cause it to stay in the low temperature zone for a long time, and the low temperature zone is conducive to the surface diffusion of the crystal structure and will cause particle coarsening, resulting in poor battery performance. In addition, it is not conducive to improving experimental efficiency and mass production. Therefore, the heating rate of the heat treatment is controlled between 1 and 5°C / min, among which 1°C / min is preferred.
[0053] In the embodiments of the present application, the temperature of the heat treatment is 500-800°C.
[0054] Specifically, the embodiments of the present application take into account that the temperature of the heat treatment will affect the conductivity of LiMPO4. Secondly, if the temperature is too high, the Li3PO4 material structure will collapse and decompose, and it cannot be effectively coated on the surface of the lithium supplement agent; if the temperature is too low, the coating phase cannot be formed and it is difficult to achieve the metal ion doping effect, so the heat treatment temperature is controlled between 500 and 800°C.
[0055] In the embodiments of the present application, the heat treatment time is 5 to 15 hours.
[0056] The time of heat treatment has an impact on the amount of crystal precipitation, crystal size, number of crystal nuclei, and crystal morphology and structure of the lithium supplement crystal. Specifically, the average particle size of the microcrystalline glass will increase with the extension of the heat treatment time, and the amount of crystal precipitation will increase, showing a trend of first increasing and then decreasing. When the heat treatment time reaches a certain value, the average particle size reaches a maximum value. Therefore, setting a suitable crystallization time for heat treatment helps to promote the formation and growth of crystals, but too long a heat treatment time may cause excessive growth or rearrangement of crystals, which will affect the crystal structure of the lithium supplement, thereby affecting the performance of the lithium supplement. With the increase of the heat treatment time, the number of crystal nuclei gradually increases, thereby affecting the microstructure and performance of the lithium supplement crystal. In the embodiment of the present application, when preparing the lithium supplement, by adjusting the heat treatment time, the growth and transformation process of the crystal can be effectively regulated, thereby controlling the formation of the lithium supplement crystal phase, and achieving the purpose of affecting the electrochemical properties of the lithium supplement.
[0057] In addition, the embodiment of the present application forms a new layer of fast ion conductor Li3PO4 phase on the surface of Li2O through a two-step method of ball milling combined with heat treatment. The fast ion conductor Li3PO4 phase has high conductivity, excellent electrochemical activity characteristics, and good coating effect, which can promote the contact between the lithium supplement agent and the positive electrode and improve the cycle and rate performance of the battery.
[0058] An embodiment of the present application also provides an all-solid-state battery, comprising any of the above-mentioned lithium supplements.
[0059] The all-solid-state battery provided in the embodiment of the present application comprises a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode material comprises any one of the lithium supplement agents disclosed in the embodiment of the present application, wherein the content of the lithium supplement agent in the positive electrode material is 0.1-10%, and the positive electrode material further comprises NCM ternary, wherein the NCM refers to three materials of nickel (Ni), cobalt (Co), and manganese (Mn), and the NCM material includes but is not limited to NCM811, NCM622, NCM523, etc., and the mixing method of mixing the lithium supplement agent in the positive electrode material is preferably selected from ball milling, grinding, powder mixing, etc.; the electrolyte is preferably selected from Li7P3S 11 , Li6PS5Cl, Li3PS4, Li7P2S8I, Li 10 GeP2S 12 The negative electrode is preferably selected from one of lithium metal, lithium indium alloy, graphite, silicon or silicon alloy, and silicon dioxide.
[0060] The present invention has no special requirements for the preparation of the battery, and the conventional preparation method of the all-solid-state lithium battery in the art can be adopted. The specific preparation process is well known in the field of solid-state batteries and will not be described in detail here.
[0061] The present invention will be described in detail below through comparative examples and examples.
[0062] The technical solution of the present application is described below in conjunction with specific embodiments.
[0063] According to the following steps, the Li2O-M@Li3PO4 in this embodiment and comparative examples 2-7 is applied to the ternary material to assemble an all-solid-state battery. The mass of the electrolyte layer is 150 mg, and the positive electrode is ground evenly according to the mass ratio of NCM811: solid electrolyte: Li2O-M@Li3PO4 lithium supplement reagent: conductive agent = 80:14:5:1, and the positive electrode active material loading is 10 mg / cm 2 The negative electrode was ground evenly according to the mass ratio of graphite: solid electrolyte = 60:40, and the negative electrode active material loading was 8 mg / cm 2 . Solid-state batteries were assembled in the order of positive electrode / electrolyte layer / negative electrode for charge and discharge tests. The voltage window for battery charge and discharge is 2 to 4.3 V. The cycle test was performed at 0.5C charge / 0.5C discharge, 100 cycles, charge and discharge tester (CT4008-5V10mA), Shenzhen Xinwell Electronics Co., Ltd. The charge and discharge test results of the all-solid-state batteries of the embodiments and comparative examples are shown in Table 1.
[0064] Example 1
[0065] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0066] Li2O and LiNiPO4 were weighed at a mass ratio of 1:0.2, and 10g of Li2O and 2g of LiNiPO4 were added to the ball mill. The equipment used was a Lai Chi-PM200 ball mill with a sealed zirconia-lined stainless steel tank. The ball milling speed was 200rpm, the ball milling time was 40h, the ball milling ball was made of zirconia, the ball milling ball size was φ1mm, and the mass ratio of the raw material to the ball milling ball was 1:10. After the ball milling was evenly mixed, the first intermediate product was obtained, which was poured into a crucible and transferred to a muffle furnace for heat treatment. The heat treatment temperature was 550℃; the heat treatment time was 10h, the heat treatment heating rate was 1℃ / min, and the inert gas used was Ar. Finally, the target lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0067] Example 2
[0068] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0069] Li2O and Li3V2(PO4)3 were weighed at a mass ratio of 1:0.1, and 10g of Li2O and 1g of Li3V2(PO4)3 were added to the ball mill. The equipment used was a Lai Chi-PM200 ball mill with a sealed zirconia-lined stainless steel tank. The ball milling speed was 250rpm, the ball milling time was 50h, the ball milling ball was made of zirconia, the ball milling ball size was φ1mm, and the mass ratio of the raw material to the ball milling ball was 1:15. After the ball milling was evenly mixed, the first intermediate product was obtained, which was poured into a crucible and transferred to a muffle furnace for heat treatment. The heat treatment temperature was 580℃, the heat treatment time was 12h, the heat treatment heating rate was 1℃ / min, and the inert gas used was Ar. Finally, the target lithium supplement material Li2O-V@Li3PO4 was obtained.
[0070] Example 3
[0071] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0072] Li2O and LiCoPO4 were weighed at a mass ratio of 1:0.15, and 10g of Li2O and 1.5g of LiCoPO4 were added to the ball mill. The ball milling speed was 280rpm, the ball milling time was 60h, the ball milling ball was made of zirconium oxide, the ball milling ball size was φ1mm, and the mass ratio of raw materials to ball milling balls was 1:20; after the ball milling was evenly mixed, the first intermediate product was obtained, and the first intermediate product was poured into a crucible and transferred to a muffle furnace for heat treatment. The heat treatment temperature was 590℃, the heat treatment time was 13h, the heat treatment heating rate was 1℃ / min, and the inert gas used was Ar. Finally, the target lithium supplement material Li2O-Co@Li3PO4 was obtained.
[0073] Example 4
[0074] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0075] Li2O and LiFePO4 were weighed at a mass ratio of 1:0.25, and 10g of Li2O and 2.5g of LiFePO4 were added to a ball mill. The speed of the ball mill was 300rpm, the time of the ball mill was 70h, the material of the ball mill was zirconia, the size of the ball mill was φ1mm, and the mass ratio of the raw material to the ball mill was 1:10. After the ball mill was evenly mixed, the first intermediate product was obtained, and the first intermediate product was poured into a crucible and transferred to a muffle furnace for heat treatment. The heat treatment temperature was 550℃, the heat treatment time was 12h, the heat treatment heating rate was 1℃ / min, and the inert gas used was Ar. Finally, the target lithium supplement material Li2O-Fe@Li3PO4 was obtained. Figure 2This is the EDS diagram of Li2O-Fe@Li3PO4. Figure 3 This is a relationship diagram between the number of cycles and specific capacity of solid-state batteries containing Li2O-Ni@Li3PO4, Li2O-V@Li3PO4, Li2O-Co@Li3PO4, Li2O-Fe@Li3PO4 and solid-state batteries without lithium supplements.
[0076] Example 5
[0077] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0078] Compared with Example 1, the mass of Li2O remains unchanged, the mass ratio of Li2O and LiNiPO4 is changed to 1:0.1, and other conditions remain unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 is obtained.
[0079] Example 6
[0080] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0081] Compared with Example 1, the mass of Li2O remains unchanged, the mass ratio of Li2O and LiNiPO4 is changed to 1:1, and other conditions remain unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 is obtained.
[0082] Example 7
[0083] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0084] Compared with Example 1, the ball milling speed was changed to 100 rpm, and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0085] Example 8
[0086] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0087] Compared with Example 1, the ball milling speed was changed to 300 rpm, and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0088] Example 9
[0089] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0090] Compared with Example 1, the ball milling time was changed to 30 h, and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0091] Example 10
[0092] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0093] Compared with Example 1, the ball milling time was changed to 70 h, and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0094] Embodiment 11
[0095] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0096] Compared with Example 1, the ball-to-material ratio was changed to 20:1, and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0097] Example 12
[0098] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0099] Compared with Example 1, the ball-to-material ratio was changed to 40:1, and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0100] Embodiment 13
[0101] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0102] Compared with Example 1, the heat treatment temperature was changed to 500° C., and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0103] Embodiment 14
[0104] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0105] Compared with Example 1, the heat treatment temperature was changed to 650° C., and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0106] Embodiment 15
[0107] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0108] Compared with Example 1, the heat treatment temperature was changed to 800° C., and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0109] Example 16
[0110] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0111] Compared with Example 1, the heat treatment time was changed to 5 h, and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0112] Embodiment 17
[0113] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0114] Compared with Example 1, the heat treatment time was changed to 10 h, and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0115] Embodiment 18
[0116] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0117] Compared with Example 1, the heat treatment time was changed to 15 h, and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0118] Embodiment 19
[0119] This example is used to illustrate a lithium supplement and a preparation method thereof of the present invention.
[0120] Compared with Example 1, the heating rate of the heat treatment was changed to 5°C / min, and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0121] Comparative Example 1
[0122] No lithium supplement reagent is added when assembling the all-solid-state battery, as follows:
[0123] The mass of the electrolyte layer is 150 mg. The positive electrode is ground evenly according to the mass ratio of ternary: solid electrolyte: conductive agent = 85:14:1. The positive electrode active material loading is 10 mg / cm 2 The negative electrode is ground evenly according to the ratio of graphite: solid electrolyte = 60:40, and the negative electrode active material loading is 8mg / cm 2 Solid-state batteries were assembled in the order of positive electrode / electrolyte layer / negative electrode for charge and discharge tests. The voltage window for battery charge and discharge is 2 to 4.3 V. The cycle test was performed at 0.5C charge / 0.5C discharge for 100 cycles.
[0124] Comparative Example 2
[0125] Compared with Example 1, the mass of Li2O remains unchanged, the mass ratio of Li2O and LiNiPO4 is changed to 1:0.05, and other conditions remain unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 is obtained.
[0126] Comparative Example 3
[0127] Compared with Example 1, the mass of Li2O remains unchanged, the mass ratio of Li2O and LiNiPO4 is changed to 1:1.1, and other conditions remain unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 is obtained.
[0128] Comparative Example 4
[0129] Compared with Example 1, the heating rate of the heat treatment was changed to 0.5°C / min, and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0130] Comparative Example 5
[0131] Compared with Example 1, the heating rate of the heat treatment was changed to 6°C / min, and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0132] Comparative Example 6
[0133] Compared with Example 1, the heat treatment temperature was changed to 450° C., and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0134] Comparative Example 7
[0135] Compared with Example 1, the heat treatment temperature was changed to 850° C., and other conditions remained unchanged, and finally the lithium supplement material Li2O-Ni@Li3PO4 was obtained.
[0136] Table 1. Charge and discharge test results of all-solid-state batteries of the embodiments and comparative examples
[0137]
[0138] It can be seen from the above technical scheme of the embodiment of the present invention that the present invention discloses a lithium supplement agent, the chemical formula of which is Li2O-M@Li3PO4, wherein M is a metal element. The present invention inserts metal elements into lithium vacancies, and the partial lattice distortion and lithium vacancies formed are beneficial to improving the kinetic activity, and the introduction of metal elements has a positive effect on the gradual breaking of Li-O bond energy, and promotes the release of lithium elements in Li2O, thereby realizing metal element doping modification, improving the conductivity of the lithium supplement agent, reducing the first-cycle overpotential, reducing Li-O bond energy, and improving the lithium ion release ability, thereby improving the conductivity of the lithium supplement agent, and the chemical stability between the lithium supplement agent and the solid electrolyte can be improved by Li3PO4 coating, reducing side reactions, and thereby improving the kinetic performance of the lithium supplement agent, thereby improving the solid electrode / solid electrolyte bulk and interface ion transport capabilities based on the lithium supplement agent.
[0139] The above description has fully disclosed the specific embodiments of the present invention. It should be pointed out that any changes made by those skilled in the art to the specific embodiments of the present invention do not deviate from the scope of the claims of the present invention. Accordingly, the scope of the claims of the present invention is not limited to the above specific embodiments.
Claims
1. A lithium supplement, characterized in that: The chemical formula of the lithium supplement is Li2O-M@Li3PO4, where M is a metal element.
2. A lithium supplement according to claim 1, characterized in that: The M includes one of Group VB or Group VIII.
3. A method for preparing the lithium supplement according to any one of claims 1 to 2, characterized in that: The method comprises: Providing a raw material, wherein the raw material includes Li2O and LiMPO4; mixing the raw materials to obtain an intermediate product; The intermediate product is placed in an inert gas atmosphere for heat treatment to obtain the lithium supplement agent.
4. The method according to claim 3, characterized in that The mass ratio of the Li2O to the LiMPO4 is 1:(0.1-1.0).
5. The method according to claim 3, characterized in that: The mixing of the raw materials to obtain the intermediate product comprises: The raw materials are mixed by ball milling to obtain an intermediate product; The rotation speed of the ball mill is 100 to 300 rpm; The ball milling time is 30 to 70 hours.
6. The method according to claim 5, characterized in that The mass ratio of the raw material to the ball milling balls is 1:(10-40).
7. The method according to claim 3, characterized in that The heating rate of the heat treatment is 1-5°C / min.
8. The method according to claim 3, characterized in that The temperature of the heat treatment is 500-800°C.
9. The method according to claim 3, characterized in that: The heat treatment time is 5 to 15 hours.
10. An all-solid-state battery, characterized in that: A lithium supplement comprising the lithium supplement described in any one of claims 1 to 2.